A Review of Platelet-Activating Factor As a Potential Contributor to Morbidity and Mortality Associated with Severe COVID-19. (November 2021) - Klein, Mark; Dao, Vinh; Khan, Fatima
The precise mechanisms of pathology in severe COVID-19 remains elusive. Current evidence suggests that inflammatory mediators are responsible for the manifestation of clinical symptoms that precedes a fatal response to infection. This review examines the nature of platelet activating factor and emphasizes the similarities between the physiological effects of platelet activating factor and the clinical complications of severe COVID-19.